Activatable T(1) and T(2) Magnetic Resonance Imaging Contrast Agents - Tu, Chuqiao (Springer US, 2011)
Magnetic resonance imaging (MRI) has become one of the most important diagnosis tools available in medicine. Typically MRI is not capable of sensing biochemical activities. However, recently emerged activatable MRI contrast agents (CAs), whose relaxivity is variable in response to a specific parameter change in the surrounding physiological microenvironment, potentially allow for MRI to indicate biological processes. Among the various factors influencing the relaxivity of a CA, the number of inner-sphere water molecules (q) directly coordinated to the metal center, the residence time of the coordinated water molecule (τ (m)), and the rotational correlation time representing the molecular tumbling time of a complex (τ (R)) contribute strongly to the relaxivity of an activatable CA. Tuning the ligand structure and properties has been the subject of intensive research for activatable MR CA designs. This review summarizes a variety of activatable MRI CAs sensitive to common variables in microenvironment in vivo, i.e., pH, luminescence, metal ions, redox, and enzymes, etc., with emphasis on the influence of ligand design on parameters q, τ (m), and τ (R).